INTEGRASI PASAR MODAL ASEAN 6 PERIODE TAHUN 2007-2016 - Ersabathari, Ruth Valencia; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2017)
Capital market integration has become a central topic in international finance. ASEAN formulated a blueprint for an establishment of ASEAN Economic Community by 2015, and endorsed an Implementation Plan that was specifically written for the goal of capital market integration. This study aims to analyze integration among the ASEAN capital markets. This study investigates the selected six members of ASEAN (Indonesia, Malaysia, Phillipines, Singapore, Thailand and Vietnam) by using weekly data from 2007 to 2016. The study examines the stock market return interdependence. The Dynamic Conditional Correlation Multivariate-GARCH (DCC MGARCH) model is engaged to assess the dynamic structure of capital market co-movements. The results showed that ASEAN 6 capital markets are integrating. The dynamic correlation indicates that there is correlation of stock return between six members of ASEAN. Based on the result of integration, there is still a chance to diversify the portofolio in ASEAN region because Vietnam has a low correlational relationship with other countries.